Prevalence Analysis of Knowledge, Perception, Conspiration, Belief and Acceptance of The Covid-19 Vaccine in a Global Crossing Study - Dewi Ratna Sulistina (Institute of Computer Science (IOCS), 2021)
Corona Virus Disease-19 (Covid-19) is declared a world pandemic that has resulted in thousands of deaths in 216 countries around the world. The emergence of this disease at the end of December 2019 in Wuhan (China) was a result of zoonotic transmission. This study seeks to assess the acceptance of the COVID-19 vaccine in the world. The results of this research are expected to contribute to the government in formulating the best approach to implement the mass vaccination program for COVID-19 in Indonesia, as well as other countries in the world, in the future. Survey of empirical studies and analysis of articles related to the prevalence analysis of knowledge, perceptions, conspiracies, beliefs, acceptance, attitudes, behavior, willingness to pay for the covid-19 vaccine in a cross-global study. The concerns and doubts about the covid-19 vaccine were caused by factors, including: 1) the emergence of a conspiracy related to the covid-19 vaccine, including the risk of side effects of infertility, 2) misinformation on social media related to the covid-19 vaccine (untrue news / hoax), 3) tendency of parents to be more likely to receive the vaccine for themselves than their child, 4) ethnicity Blacks are almost 3 times more likely to reject the COVID-19 vaccine than white participants, 5) More than 50% of citizens are willing to pay for the vaccine and 72% feel the vaccine should first be given to health workers and high-risk groups. To increase awareness and acceptance of the importance of the covid-19 vaccine as an effort to increase immunity to prevent the onset of covid-19, efforts are needed, including: 1) a structured awareness campaign (health promotion) is needed globally, 2) policies government regarding the importance of careful fact-checking (spreading hoax news) related to vaccines, 3) a strategic approach considering various economic classes of society can be applied in developing countries, 4) increasing risk perceptions in the community, 5) developing a model for vaccine payments and subsidizing some vaccines for them those who are less capable, 6) the implementation of post-efficacy tasks in a timely and coordinated manner will make the pandemic effective and efficient